2010
DOI: 10.1007/s11064-010-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tryptophan Catabolism along the Kynurenine Pathway in Acute Ischemic Stroke

Abstract: Post-stroke inflammation may induce upregulation of the kynurenine (KYN) pathway for tryptophan (TRP) oxidation, resulting in neuroprotective (kynurenic acid, KA) and neurotoxic metabolites (3-hydroxyanthranillic acid, 3-HAA). We investigated whether activity of the kynurenine pathway in acute ischemic stroke is related to initial stroke severity, long-term stroke outcome and the ischemia-induced inflammatory response. Plasma concentrations of TRP and its metabolites were measured in 149 stroke patients at adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 38 publications
(78 reference statements)
6
73
1
1
Order By: Relevance
“…Darlington et al 96 showed increased TRP catabolism after stroke and suggest that oxidative TRP metabolism contributes to oxidative stress and brain damage. Brouns et al 95 showed a correlation between KYN/TRP ratio and stroke severity and long-term stroke outcome that did not correlate with KA/3-hydroxyanthranillic acid ratio. Mo et al 98 showed an upregulation of IDO activation in ischaemic stroke.…”
Section: Mechanisms Of Psfmentioning
confidence: 99%
“…Darlington et al 96 showed increased TRP catabolism after stroke and suggest that oxidative TRP metabolism contributes to oxidative stress and brain damage. Brouns et al 95 showed a correlation between KYN/TRP ratio and stroke severity and long-term stroke outcome that did not correlate with KA/3-hydroxyanthranillic acid ratio. Mo et al 98 showed an upregulation of IDO activation in ischaemic stroke.…”
Section: Mechanisms Of Psfmentioning
confidence: 99%
“…Following its synthesis by IDO, Kyn can be further metabolized by various enzymes (Figure 1)(1, 3234). Kynureninase produces anthranilic acid (AA) from Kyn(35, 36).…”
Section: Kynurenine Pathwaymentioning
confidence: 99%
“…The accumulation of microglial cells has been demonstrated in the HD brain [37], but the number of T-cells is not altered [38]. There is an increasing evidence of the involvement of activation of the kynurenine pathway in relation to inflammatory processes in both ischemic stroke ( [39]) and HD ( [40]). …”
Section: Neuroinflammationmentioning
confidence: 99%